2020
DOI: 10.1063/5.0012967
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of red luminescence from iron-doped β-Ga2O3 bulk crystals

Abstract: Currently, Fe doping in the ~10 18 cm-3 range is the most widely-available method for producing semi-insulating single crystalline-Ga 2 O 3 substrates. Red luminescence features have been reported from multiple types of Ga 2 O 3 samples including Fe-doped-Ga 2 O 3 , and attributed to Fe or N O. Herein, however, we demonstrate that the high-intensity red luminescence from Fe-doped β-Ga 2 O 3 commercial substrates consisting of two sharp peaks at 689 nm and 697 nm superimposed on a broader peak centered at 710 n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
(62 reference statements)
3
20
0
Order By: Relevance
“…It was suggested that the internal transitions between the 2 E and 4 A 2 states of Cr 3þ give rise to two sharp emission (or absorption) lines at around 1.78 and 1.80 eV at room temperature (RT), which were labeled as R1 and R2 lines. 18,19,[22][23][24][25][26][27][28][29][30] This conclusion was based 19,22,23,25 on a similarity of the transition energies with the internal transitions of Cr 3þ in Al 2 O 3 . [31][32][33] They were further supported by the analysis of higher-lying excited states detected in absorption 19,28 and emission 18,22,[24][25][26][27][28] spectra of Cr-doped b-Ga 2 O 3 , as well as photoluminescence excitation spectra of the R lines 24,26,28 using the Tanabe-Sugano diagrams.…”
mentioning
confidence: 99%
“…It was suggested that the internal transitions between the 2 E and 4 A 2 states of Cr 3þ give rise to two sharp emission (or absorption) lines at around 1.78 and 1.80 eV at room temperature (RT), which were labeled as R1 and R2 lines. 18,19,[22][23][24][25][26][27][28][29][30] This conclusion was based 19,22,23,25 on a similarity of the transition energies with the internal transitions of Cr 3þ in Al 2 O 3 . [31][32][33] They were further supported by the analysis of higher-lying excited states detected in absorption 19,28 and emission 18,22,[24][25][26][27][28] spectra of Cr-doped b-Ga 2 O 3 , as well as photoluminescence excitation spectra of the R lines 24,26,28 using the Tanabe-Sugano diagrams.…”
mentioning
confidence: 99%
“…Polarization dependence of emission is seen below the bandgap for all three samples. The observed red emission starting around 700 nm (1.77 eV) is due to the Fe-doped β-Ga 2 O 3 substrate on which the Si-doped β-Ga 2 O 3 films were grown 27 , 28 .
Figure 1 Polarized photoluminescence of β-Ga 2 O 3 grown on (010) Fe-doped β-Ga 2 O 3 excited at 267 nm (4.64 eV).
…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the red emission is quite ambiguous, and the literature provides three plausible explanations involving doping by transition metals or rare earth metals [ 10–14,19–21 ] or by nitrogen. [ 22,23 ] Figure 1b shows the CL spectra recorded in the region of 700 nm to provide more details in the near‐IR region of the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…This raises an important question on the origin of these transitions, which may well be due to other transition‐metal impurities such as Cr. [ 10,24 ] It is well known that even very low concentrations, of the order of ppm, of Cr can result in strong luminescence. [ 28,29 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation